Bacterial diversity associated with the brown stone centipede, Lithobius forficatus (Chilopoda, Lithobiomorpha) - Vahtera, Varpu; Rezola, Uxue; Duplouy, Anne (FINNISH ZOOLOGICAL BOTANICAL PUBLISHING BOARD, 2025)
Many associations with microbial species significantly affect the biology, ecology and evolution of the host. Yet, our understanding of the species composition of the gut microbiota remains limited for many host species. Here, we provide a new step towards filling this gap, and characterize the bacterial microbiota of 60 specimens of Lithobius forficatus, a brown stone centipede commonly found in Finland. Many specimens analysed in this study were found to have a very species-rich bacterial community, while others hosted communities clearly dominated by one bacterial species. The most abundant phylotypes included some potential pathogens such as Borrelia and Pseudomonas, a honeybee gut symbiont Gilliamella and some maternally inherited symbiotic bacteria, including Wolbachia and Rickettsiaceae. While females and males were found to carry similar bacterial communities, population had a significant effect on the bacterial community composition. Bacterial species richness did not differ between sexes or between populations in Lithobious forficatus.